Group 2 Innate Lymphoid Cells Participate in Renal Fibrosis in Diabetic Kidney Disease Partly via TGF-β1 Signal Pathway - Cuiping Liu; Ludan Qin; Jingya Ding; Luping Zhou; Chenlin Gao; Ting Zhang; Man Guo; Wei Huang; Zongzhe Jiang; Yang Long; Yong Xu (Journal of Diabetes Research)
Aim. To explore the role of group 2 innate lymphoid cells (ILC2s) in the pathogenesis of renal fibrosis in diabetic kidney disease (DKD). Methods. The proportion of ILC2s and the levels of Th2 cytokines (IL-4, IL-5, and IL-13) in the peripheral blood of normal control subjects (NC) or patients with type 2 diabetes mellitus (DM), early diabetic kidney disease (DKD1), or late diabetic kidney disease (DKD2) were analyzed by flow cytometry and ELISA. The expression of transforming growth factor-β1 (TGF-β1), fibronectin (FN), collagen1, IL-4Rα, and IL-13Rα1 in renal tubular epithelial cells (HK-2) induced by IL-4, IL-13, or high glucose was analyzed by ELISA or qPCR. Results. The proportion of ILC2s and the levels of IL-4, IL-5, and IL-13 were significantly increased in DKD patients and were positively correlated with the severity of DKD (P<0.05). The expression of TGF-β1, FN, and collagen1 was significantly upregulated in HK-2 cells induced by IL-4 or IL-13 (P<0.05). Moreover, the IL-4Rα and IL-13Rα1 mRNA in HK2 cells were increased followed by high glucose alone or combined with IL-4 or IL-13, but the differences were not statistically significant (P>0.05). However, compared with high-glucose stimulation alone, the expression of TGF-β1, FN, and collagen1 was significantly increased in HK-2 cells induced by high glucose combined with IL-4 or IL-13 (P<0.05). Conclusions. ILC2s may participate in renal fibrosis in DKD partly via TGF-β1 signal pathway.